Los sistemas de información en la gestión administrativa en el GAD Municipal de Guano. - Macas Guadalupe, Silvana Graciela (2023)
The information systems currently exist have changed the way in which both private and public organizations operate, their use entails great improvements in the management of an institution, because they automate the operational processes, they obtained support information for decision making and facilitate the achievement of competitive advantages in the organization. Public management without data does not allow making the right decisions, and the dependence of the central government on the information guaranteed by the cantonal GADs is essential to take measures that adjust to the reality and needs of each territory, likewise, each GAD must administer and provide citizens with the data associated with their management, guaranteeing the generation and provision of strategic information for local planning. That is why, the present investigation reduces how the information systems affect the administrative management in the Municipal GAD of Guano. The research was descriptive, documentary with a non-experimental design, as a data collection technique the survey was used, which had a previously approved questionnaire with Likert-type responses applied directly to the entity's administrative staff. As a result, it was obtained that the majority of the people surveyed were satisfied with the SI that currently use the GAD, in the same way each one considered that they agreed with the importance of the management, equipment and training of the SI, in addition to knowing the benefits which brings its use as the best customer service and help in administrative management, also supporting the proposal of a better IS to improve these processes. Concluding that through exhaustive research in the different bibliographical sources, it was possible to theoretically base on the IS and administrative management, clarifying the definition of each one, in addition, the use of the Software provided by SAP will be known, whose success stories validate its use in the companies.